Delayed Awareness of the History of Barium Examination: Perforated Barium Appendicitis. (9th April 2017) - Saigusa, Susumu; Ohi, Masaki; Oki, Satoshi; Ichikawa, Takashi; Kobayashi, Minako; Inoue, Yasuhiro; Miki, Chikao
Abstract : A 41-year-old man presented to our hospital with lower abdominal pain and a high-grade fever. Physical examination revealed rebound tenderness and guarding in the lower abdomen. Abdominal X-ray examination showed a radiopaque object in the right lower quadrant of the abdomen. Abdominal computed tomography (CT) demonstrated that the object had a strong artifact with over 10, 000 Hounsfield units, as well as ascites around the terminal ileum. We diagnosed acute peritonitis with a suspicion of the perforation due to unknown foreign body and performed an emergency laparotomy. Operative findings showed a contained perforation of a phlegmonous appendicitis, and appendectomy was performed. The resected specimen demonstrated that the appendix contained a fecalith, and histopathological examination showed the crystal structure of barium sulfate in the lumen of the appendix. Unfortunately, we did not obtain the history of screening for gastric cancer using a barium examination one month prior to our appendectomy. Our experience demonstrates the importance of establishing a history of barium examinations of the gastrointestinal tract in a patient with a radiopaque object in the right lower quadrant of the abdomen for early diagnosis of barium appendicitis. Additionally, early diagnosis of barium appendicitis may affect the selection of surgical procedures.